Ejercicio de Negociación UNA DECISION DE RUTINA - Tejada Oshiro, Carlos (1992)
It shows an exercise whose objective is to get the students or participants to design the strategy they will follow during a negotiation process, taking into account the basic principles of a price negotiation. It simulates a typical negotiation between a buyer and a seller, each of whom has information that the other does not know. Each party must negotiate the price at which it will be willing to enter into the transaction.  A second objective is to record the evolution of the negotiation process in order to measure the strength and sequence of the arguments, as well as the style of the negotiation. To this end, the instructor's guide suggests that the participant should define his strategy, prepare the arguments with which he will support it and define his negotiation style.